Intraocular Metallic Foreign Body: Role of Computed Tomography - Suthar Pokhraj P.; Patel Jigar J.; Mehta Chetan; Patel Narottam A. (Journal of Clinical and Diagnostic Research, 2014)
Orbital foreign bodies remain a serious diagnostic problem, despite development of diagnostic imaging techniques. Non-metallic orbital foreign body will not be detected in routine x-ray. Here we are presenting a case of 32-year-old male presented with acute pain in left eye immediately after he had been pounding a metal object with a metal chisel. Following this event patient develop blurring of vision in left eye with tearing. Patient’s vision in left eye was found to be hand motion with conjunctiva mildly injected, left corneal central 1 mm Seidelnegative full-thickness laceration and dense traumatic cataract was seen on ocular examination. Dilated fundus examination of left eye was not possible due to traumatic cataract. Vitreous hemorrhage, vitreous detachment and a echogenic foreign body present in posterior segment in B–Scan sonography. Well-defied hyperdense foreign body producing streak artifacts with vitreous hemorrhage was seen in the posterior chamber of left eyeball in CT orbit. The patient was diagnosed with a corneal laceration, traumatic cataract, vitreous hemorrhage and a metallic intraocular foreign body. He was brought to the operating room urgently for corneal laceration repair, pars plana vitrectomy, lensectomy, and removal of the metallic intraocular foreign body done.